ANALISIS USABILITY TESTING PADA SISTEM SIMATRA UKI TORAJA MENGGUNAKAN HEURISTIC EVALUATION DAN SYSTEM USABILITY SCALE - Herdianto Bilma Bunga; Adi Nugroho (Universitas Citra Bangsa, 2025)
Operational testing is crucial in evaluating the usability of an academic information system. However, there is still a lack of studies specifically analyzing the usability level of SIMATRA UKI Toraja. Therefore, this study aims to assess the usability of SIMATRA UKI Toraja using the Heuristic Evaluation method and the System Usability Scale (SUS). The evaluation was carried out by four evaluators using Nielsen’s ten heuristic principles and involved 384 respondents for the SUS assessment. The Heuristic Evaluation identified five major issues related to system status visibility, navigation, and usage flexibility. Meanwhile, the SUS testing resulted in a usability score of 81.25, categorized as acceptable. These findings indicate that SIMATRA still has several shortcomings in terms of user interface and user experience. Improvement recommendations are provided to enhance user efficiency and satisfaction. The results of this study may serve as a reference for further development of academic systems to better respond to user needs.